The impact of biodiesel blend ratio on vehicle performance and emissions - Bannister, C.D.; Pickford, W.; Brown, A.; Chrysafi, S.S.; Price, P.; Chuck, C.J.; Ali, Hapipah Mohd; Hawley, J.G. (2010)
Biodiesel is synthesized via the transesterification of triglycerides contained within vegetable, animal, or waste oils. First-generation biofuels are not the solution to global transport energy needs; however, biodiesel does have a role to play in reducing greenhouse gas emissions from the transport sector, so long as necessary production can be achieved in a sustainable manner without negative impact on plant and animal biodiversity. The biodiesel content within diesel sold to consumers is set to increase in the future, with implications on vehicle fuel consumption, emissions, and base engine durability. This study examines the effects of increasing the biodiesel blend ratio on the performance and emissions of a production vehicle equipped with a common-rail direct-injection diesel engine, evaluated on a chassis rolls dynamometer, at various ambient temperatures. Results obtained show that reductions in engine-out carbon monoxide and hydrocarbon emissions do not always translate to lower tailpipe emissions as reduced exhaust gas temperatures at higher blend ratios lead to reduced catalyst conversion efficiencies and higher total cycle emissions. Catalyst conversion efficiencies for carbon monoxide and hydrocarbons over the New European Drive Cycle (NEDC) are reduced by 9-19 per cent (depending on the ambient temperature) for a 50:50 blend (B50) compared with the petroleum diesel (B0) baseline. Increasing the blend ratio caused a linear decrease in the vehicle's maximum tractive force. This reduction was of the order of 5 per cent for a B50 blend at low vehicle speeds and 6-10 per cent at higher speeds, which is greater than Would be expected on the basis of the differences in calorific values. Over the NEDC, the fuel consumption was found to increase with increasing blend ratio.